Language Style Analysis in The Hunger Games Movie - Febriana, Putu Adelia; Sri Rahayuni, Ni Ketut; Primahadi Wijaya Rajeg, Gede (Humanis, 2024)
This study analyzes the language style used in the utterances of the main characters (i.e., Katniss Everdeen and Peeta Mellark) in The Hunger Games Movie. The relevant data was obtained using a qualitative method, especially the documentation method. This study also presents the language style most often used by the main characters, focusing on the five language style features and functions proposed by Martin Joos (1976): formal style, consultative style, casual style, intimate style and frozen style. Overall, we found that the casual style is more often used than the other language styles. More specifically, there are 70 data that convey particular language styles, the distribution of which is as follows: 1 frozen style data, 18 formal style data, 10 consultative style data, 27 casual style data, and 14 intimate style data.